Decrease of muscle strength in vascular access hand due to silent ischaemia - Kmentova, Tereza; Valerianova, Anna; Kovarova, Lucie; Lachmanova, Jana; Hladinova, Zuzana; Malik, Jan (The journal of vascular access, 2018)
BACKGROUND:: Creation of vascular access leads to considerable local haemodynamic changes with decreased hand perfusion. Distal limb tissues then represent a model of hand ischaemia effect on muscles. The aim of our study was to investigate how the presence of vascular access influences the hand muscle strength in end-stage renal disease patients. METHODS:: We included 52 chronically haemodialysed patients with upper limb access without clinical signs of hand ischaemia. Muscle strength was evaluated by dynamometry. Finger pressure was measured on the second and fourth fingers and averaged for further analysis. Thenar tissue oxygenation (rSO2) was analysed using near-infrared spectroscopy. All examinations were performed in both the hands. Basic laboratory analysis was added. Data were processed with unpaired t-test and correlation analysis. RESULTS:: Hands with dialysis access had lower values of handgrip strength (54.2 ± 29.1 lbs vs 48.6 ± 23.4 lbs, p = 0.0006), systolic finger pressure (127.1 ± 32.0 mmHg vs 101.4 ± 31.6 mmHg, p < 10-8) and of thenar rSO2 (45.8% ± 12.9% vs 42.5% ± 13.3%, p = 0.002). Muscle strength (handgrip) was directly related to the thenar oxygenation ( r = 0.36; p = 0.014) and to the finger systolic pressure ( r = 0.38; p = 0.007) on the access extremity. On the extremity without dialysis access, handgrip strength was inversely related to patient's age ( r = -0.41, p = 0.003), dialysis vintage ( r = -0.32, p = 0.02) and red cell distribution width ( r = -0.37, p = 0.01). CONCLUSION:: The presence of dialysis access leads to the decrease of finger pressure, oxygenation, and also muscle strength even in the absence of clinically overt hand ischaemia. All these parameters are interrelated. This study underlines the consequences of inadequate muscle perfusion.
Keywords: hand ischaemia; arteriovenózní zkrat; Hand Strength; ischemie; senioři; Aged; Male; hemodynamika; dialýza ledvin; lidé; lidé středního věku; Humans; kyslík; Ischemia; Middle Aged; Oxygen; Arteriovenous Shunt, Surgical; Renal Dialysis; muscle strength; mužské pohlaví; Haemodialysis; ruka; vascular access; Hand; Hemodynamics; regionální krevní průtok; ženské pohlaví; chronické selhání ledvin; Regional Blood Flow; síla ruky; Female; Kidney Failure, Chronic; hand muscle; hand tissue oxygenation